Know Your Heritage: Exploring the Effects of Fit in Cultural Knowledge on Chinese Canadians’ Heritage Identification - Zhang, Rui; Noels, Kimberly A.; Lalonde, Richard N. (Frontiers in Psychology, 2018)
In the present research, we introduce the notion of fit in cultural knowledge (FICK) – which we define as a match between the self and others in representing a cultural tradition. For ethnic minorities, FICK can be manifested in different degrees of matching their personal beliefs about their heritage culture with outgroup as well as ingroup beliefs about their heritage culture. We conducted two studies with the objective of exploring the potentially negative effects of FICK on Chinese Canadians’ heritage identification. In both studies, Chinese Canadian university students (N = 102; N = 156) indicated their personal beliefs about what values are normative in Chinese culture. Ingroup beliefs were assessed by beliefs about Chinese values that Chinese Canadians ascribed to their parents (Study 2), whereas outgroup beliefs were assessed by beliefs about Chinese values that were held by Euro-Canadians (Study 1) or that Chinese Canadians ascribed to Euro-Canadians (Study 2). The main findings based on a series of path models are as follows: 1) a stronger FICK generally predicted lower Chinese identification (centrality, ingroup ties, and affect), yet those negative effects were largely manifested in the openness to change versus conservation rather than in the self-transcendence versus self-enhancement value dimension. 2) the negative effects could be explained by Chinese Canadians' experience of bicultural conflict (Study 1) and the frustration of continuity, meaning, and belonging identity motives (Study 2), suggesting that it matters which specific views of Chinese culture are matched in FICK. 3) Individuals who agreed with the perceived outgroup beliefs, and parental beliefs to a lesser extent, were more likely to apply the model minority stereotype to other Chinese Canadians (Study 2). Taken together, those findings demonstrate the challenges FICK presents to heritage identity maintenance among Chinese Canadian young adults. Implications for enculturation and cultural fit are discussed.